2004
DOI: 10.1136/ip.2003.004119
|View full text |Cite
|
Sign up to set email alerts
|

A quantification of preventable unintentional childhood injury mortality in the United States

Abstract: Objective: To calculate the preventable fraction of unintentional childhood injury deaths in the United States. Design: Ecological study of cause specific unintentional childhood injury mortality rates across the 50 states (and the District of Columbia) of the United States (US) over the 10 year period 1989-98. Methods: The internet accessible database from the National Center for Injury Prevention and Control was used in order to estimate unintentional childhood (0-14 years) injury mortality rates by external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 11 publications
2
31
0
1
Order By: Relevance
“…Our study results are similar to those reported in Western countries regarding a signifi cantly decreasing trend in mortality rates due to total injuries and unintentional injuries among children of 0-17 years. [19] The injury mortality rates of males are twice as high as that of females worldwide. [19,20] In the United States, boys were more commonly injured, [21] as we found in this study with a male to female death ratio of 3.4:1 for all types of injuries leading to death.…”
Section: Discussionmentioning
confidence: 99%
“…Our study results are similar to those reported in Western countries regarding a signifi cantly decreasing trend in mortality rates due to total injuries and unintentional injuries among children of 0-17 years. [19] The injury mortality rates of males are twice as high as that of females worldwide. [19,20] In the United States, boys were more commonly injured, [21] as we found in this study with a male to female death ratio of 3.4:1 for all types of injuries leading to death.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the risk groups and risk settings for all kinds of accidents are the main factors that influence an increase in socioeconomic loss and also a decrease in the quality of human resources [16,17]. Therefore, an increase in active governmental intervention is needed to ensure accident prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Si le taux standardisé global est de 27,9/100 000 en France, on constate une mortalité significativement supérieure à la moyenne dans quatre régions (Nord-Pas-de-Calais, Franche-Comté, Bretagne et Auvergne), et à l'opposé significativement plus faible en Ile-deFrance, Aquitaine et Provence-Alpes-Côte-d'Azur. Faut-il rapprocher ces faits des études sociologiques faites aux États-Unis montrant que la fréquence des accidents est plus faible dans la région nord-est, où le niveau d'instruction des parents est plus élevé [3] ?…”
Section: Résultats Chiffrésunclassified